Recurrent nasopharyngeal carcinoma with a rare presentation of anterior chest wall swelling - Rosla, Luqman; Eshamsol, Kamar; Rohaida, Ibrahim; Asha'ari, Zamzil Amin (Japan International Cultural Exchange Foundation, 2017)
Objective: To report a unique case of recurrent nasopharyngeal carcinoma (NPC) presenting as the anterior chest wall swelling. Design: Case report. Methodology: Medical record review. Results: A 41-year-old Chinese man was diagnosed with nasopharyngeal carcinoma and initially treated with chemoradiotherapy for the primary tumor. He was clinically completely responded well to the treatment given. He presented with painful anterior chest wall swelling, 30 months after completion of chemo radiotherapy. CT thorax revealed lung metastases with direct invasion of the lung metastases to the anterior chest wall. Biopsy of the thoracic lesion showed the same histological features as the primary tumor. Conclusion: To our knowledge, this was the first case of recurrent NPC presented with chest wall swelling in the literature. The case highlights the different systemic manifestation of NPC.